: Factors influencing poor pass rate among Ordinary Level accounting learners in Munyikwa cluster. - Mbangana, Terryson (Midlands State University, 2020)
The study focused on the factors influencing the poor pass rate among Ordinary level Accounting learners in Munyikwa cluster. The researcher used descriptive survey in order get a detailed information on participants in relation to poor pass rate. Purposive sampling technique was used to select heads of schools, accounting teachers and form four accounting learners who were participants in the study. The researcher used semi structured interviews, observation schedule and document analysis schedule to generate data for the study. Thematic approach was used to analyse data generating generated. The findings were that, teacher qualifications and inexperience, learner’s negative attitudes, lack of teaching and learning resources as well as teacher centred approaches contribute to the poor pass rate by learners in Accounting. Some of the recommendations are that, further training for teachers, career guidance session for learners the value of accounting and conducting fundraising activities to mobilise resources.